Hepatoprotective Activity of Ethanol Extract of Figs Leaves (Ficus carica L.) with SGOT & SGPT Parameters in Sprague Dawley Female Rats Induced by Paracetamol: Efek Hepatoprotektif Ekstrak Etanol Daun Tin (Ficus carica L.) dengan Parameter SGOT dan SGPT pada Tikus Betina Sprague Dawley yang Diinduksi Paracetamol - Kurniawan, Muhammad Fariez; Wardany, Herdita Nugraheny Kusuma (Universitas Tadulako, 2021)
Background: Long-term usage of paracetamol damages liver cells characterized by the increasing levels of Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxaloacetic Transaminase (SGOT). Figs (Ficus carica L.) leaves contain high flavonoid compounds that able to act as hepatoprotector agents which inhibited the process of liver damage. Objectives: This study aims to determine the dose characteristics and hepatoprotective activity of figs (Ficus carica L.) leaves extract. Material and Methods: The hepatoprotective activity of figs extract (Ficus carica L.) was determined by measuring SGPT & SGOT levels in rat blood. 42 rats were prepared, divided into 7 groups: normal control group, negative control given paracetamol with a dose 40 mg/200 g BW, positive control given hepamaxÂ®, base control given Na CMC, and 3 test dose groups given figs leaves extract with a dose of 40 mg/200 g BW, 80 mg BW/200 g BW and 160 mg/200 g BW. The treatment was carried out for 14 consecutive days. Paracetamol was given for 14 days, while positive control, 3 test dose groups and base control were given on day 7 to day 14. Rats blood samples were taken through the orbital sinuses on day 1, day 5, day 10 and day 14 after treatment began. SGPT & SGOT levels were determined using spectrophotometry with analytical methods using specific SGPT & SGOT reagent kits. Results: The results showed that the leaves extract of figs (Ficus carica L.) proved to be able to reduce the levels of SGPT & SGOT with the most potent dosage was 40 mg/200 g BW. However, the reduction of SGPT & SGOT levels were not significantly different from other treatments. Conclusions: Figs (Ficus carica L.) leaves extract showed activity as a hepatoprotective agent, based on the reduction of SGPT & SGOT levels in rat after 14 days of treatment.